Unveiling Misconceptions: A Multilocation Study on First-Year College Students in Indonesia - Muliyani, Riski; Suhandi, Andi; Prima, Eka Cahya; Muslim, Muslim (Journal of Teaching and Learning Physics, 2024)
The aim of this research is to determine whether there are any misconceptions among first-year students regarding the concepts of heat and temperature. This study employs a descriptive research design. The sample used in this study consists of 224 first-year students from both public and private universities in the cities of Singkawang, Bima, Madiun, and the districts of Sumedang, Sintang, and Bandung. Data were collected through a g-form using a four-tier test instrument. The research results indicate that the percentage of misconceptions among students on the concepts of temperature and heat is highest in the sub-topic "Objects with higher temperature definitely have more heat content compared to objects with lower temperature," reaching 62.1%, and the lowest misconception in the sub-topic "Water at a temperature of 0°C has entirely turned into ice," reaching 40.6%. It is hoped that these findings can be utilized by lecturers and teachers in addressing the subtopic of heat and temperature, which is known to have many possible misconceptions. As a result, educators can employ effective instructional strategies to address their students' misunderstandings about heat and temperature